All Days 2012
DOI: 10.2118/153528-ms
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Charged Particles as an Efficient Way to Improve Rheological Properties of Heavy Asphaltic Petroleum Fluids

Abstract: High energy electron particles were utilized to improve the rheological properties of heavy asphaltic petroleum fluids and upgrade them into lighter, and more utilizable, fluids. Heavy oil reserves, as one of the most abundant sources of energy, have attracted considerable attention during the last decades. However, high viscosity of such fluids always poses problems during production and transportation operations. Complex hydrocarbon molecules in heavy petroleum fluids can be affordable sources of energy if w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Although application of ionizing particles in petroleum industry has had a rapid growth during the recent decades, quite a few works have investigated the rheological property changes that are brought about because of radiation-induced reactions. Alfi et al showed that electron-induced thermal cracking of heavy petroleum fluids results in products with lower viscosities than the thermal cracking cases.…”
Section: Introductionmentioning
confidence: 99%
“…Although application of ionizing particles in petroleum industry has had a rapid growth during the recent decades, quite a few works have investigated the rheological property changes that are brought about because of radiation-induced reactions. Alfi et al showed that electron-induced thermal cracking of heavy petroleum fluids results in products with lower viscosities than the thermal cracking cases.…”
Section: Introductionmentioning
confidence: 99%